2012
DOI: 10.1371/journal.pone.0042513
|View full text |Cite
|
Sign up to set email alerts
|

TGF-Beta Induced Erk Phosphorylation of Smad Linker Region Regulates Smad Signaling

Abstract: The Transforming Growth Factor-Beta (TGF-β) family is involved in regulating a variety of cellular processes such as apoptosis, differentiation, and proliferation. TGF-β binding to a Serine/Threonine kinase receptor complex causes the recruitment and subsequent activation of transcription factors known as smad2 and smad3. These proteins subsequently translocate into the nucleus to negatively or positively regulate gene expression. In this study, we define a second signaling pathway leading to TGF-β receptor ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
130
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 136 publications
(146 citation statements)
references
References 52 publications
(92 reference statements)
14
130
1
1
Order By: Relevance
“…It is assumed that PSmadL attenuates R-Smad to inhibit its association with C-Smad which causes the negative regulation of TGF-β/Smad signaling by the MAPK pathway [19]. However, this argument cannot explain the opposite effect of the MAPK pathway on TGF-β/Smad signaling reported in several sources in the literature [1,9,[11][12][13]27]. As previously mentioned, some studies suggest that the levels of Ras activity could dictate the outcome of the cross talk [18,19].…”
Section: Potential Crosstalk Mechanismsmentioning
confidence: 98%
See 4 more Smart Citations
“…It is assumed that PSmadL attenuates R-Smad to inhibit its association with C-Smad which causes the negative regulation of TGF-β/Smad signaling by the MAPK pathway [19]. However, this argument cannot explain the opposite effect of the MAPK pathway on TGF-β/Smad signaling reported in several sources in the literature [1,9,[11][12][13]27]. As previously mentioned, some studies suggest that the levels of Ras activity could dictate the outcome of the cross talk [18,19].…”
Section: Potential Crosstalk Mechanismsmentioning
confidence: 98%
“…Experiments by Hough et al [1] and Funaba et al [12] showed that most of PSmadL was found in the nucleus of cell fibroblasts. These data do not preclude the possibility of cytoplasmic phosphorylation of Smad2 in the linker region, followed by a rapid nuclear translocation [13,35].…”
Section: Potential Crosstalk Mechanismsmentioning
confidence: 98%
See 3 more Smart Citations